Local scour downstream of an unsubmerged weir with an apron - Leu, Michelle Yihui (2019)
Many studies have been done on local scouring located downstream of sluice gates and submerged weir. However, not as much studies have been done to study the effects of local scouring downstream of an unsubmerged weir. It is important to study local scouring for the different hydraulic structures as the local scouring would result in the instability of the structure which can be very damaging and might risk the lost of lives. Thus, studying how the different parameters would affect the scour profile can help to make better judgements when constructing any hydraulic structures. This would also help to better study the different types of protection in which could be set in place to reduce the scouring effect from occurring rapidly. In this Final Year Report, the primary study is to find out how the different parameters: tailwater depth, flowrate and apron length would affect the profile of a local scour occurring downstream of an unsubmerged weir. Experiments set at different parameters have been conducted and the video of the scouring have been recorded for analysis. On top of studying how the three parameters have effect on local scour, the occurrence of jet-flipping would also be investigated. Jet-flipping, bed regime and surface regime are currently the three primary flow patterns observed. The bed regime is the flow pattern whereby the incoming jet attached itself to the channel bed and it would start to erode the bed forming a “digging” action. Surface regime is the flow pattern whereby the incoming jet attached itself to the free surface of the channel and a “refilling” action could be observed and the sediments would start to refill back and spread out evenly in the scour hole. During jet-flipping the flipping action where the bed jet changes over to a surface jet could be observed. This change occurs abruptly and caused a significant change the scour development.